The Effects of Dietary Bacillus amyloliquefaciens TL106 Supplementation, as an Alternative to Antibiotics, on Growth Performance, Intestinal Immunity, Epithelial Barrier Integrity, and Intestinal Microbiota in Broilers - Chengling Bao; Wenxiu Zhang; Jian Wang; Yajing Liu; Heng Cao; Feiyu Li; Suozhu Liu; Zhengda Shang; Yunhe Cao; Bing Dong (Animals, 2022)
A total of 240 1-day-old Arbor Acres male broilers were randomly divided into five dietary treatments (control feed (CON), supplemented with 75 mg/kg aureomycin (ANT), supplemented with 7.5 × 108 CFU/kg (Ba1) and 2.5 × 109 CFU/kg (Ba1), and 7.5 × 109 CFU/kg (Ba3) Bacillus amyloliquefaciens TL106, respectively) to investigate the probiotic effect of TL106 instead of antibiotics in broilers. On days 1–21, the average daily gain of broilers in the Ba groups was increased compared with the CON group (p < 0.05). In addition, the feed/gain ratio of broilers in the Ba groups was lower than that of broilers in the CON and ANT groups on days 22–42 and days 1–42 (p < 0.05). Compared with the CON group, dietary TL106 increased the digestibility of crude fiber and crude protein (p < 0.05), and the effect was similar to that of the ANT group. The levels of IL-1β, IFN-γ, and IL-6 in serum, jejunum, and ileum of broilers fed TL106 were decreased compared with the control group (p < 0.05). The mRNA expression of tight junction proteins in broilers of ANT and Ba groups was higher than the control group (p < 0.05). After 21 days, villus height and the ratio of villus height to crypt depth of duodenum and jejunum of broilers fed TL106 were higher than the control group (p < 0.05). The concentrations of short-chain fatty acids such as lactate, acetate, propionate, and butyrate in cecal digesta of broilers dietary TL106 were higher than the control group (p < 0.05). The supplementation with TL106 altered the compositions and diversity of the cecal microbiota of broilers. Moreover, supplementation with TL106 improved the ratio of Firmicutes to Bacteroidetes and decreased the relative abundance of Proteobacteria on days 21 and 28, while the abundance of Peptostreptococcaceae, Ruminococcaceae and Lactobacillaceae was increased. On days 35 and 42, broilers fed TL106 had an increased total abundance of Firmicutes and Bacteroidetes and decreased abundances of Lactobacillaceae, while the abundance of Barnesiellaceae was increased. In conclusion, dietary supplementation with TL106 improved the broiler’s growth performance, immune response capacity, gut health, modulated development, and composition of the gut microbiota in broilers. It is suggested that Bacillus amyloliquefaciens TL106 may be a suitable alternative to in-feed antibiotics to improve broiler health and performance.